A Literature Review: The Implementation of the Borg & Gall Development Model in Science Learning - Johana Aulina Rahmatin; Sri Aprilia Nur Larasati; Rita Alawiyah (Indonesian Publication Center, 2025)
Implementing the Borg & Gall model in science education is highly significant for creating educational products that are adaptive, relevant, and based on real-world needs. This research utilized a literature review method with data processed using descriptive analysis. Three relevant journals were identified for this study. Based on the literature review conducted on these three journals, the development of instructional media using the Borg & Gall development model in science learning had a positive impact on improving student learning outcomes. An interesting area for future research would be to apply the Borg & Gall model to other study focuses or subject areas to further develop knowledge regarding the Borg & Gall development model.